Quantum Safe Cryptography using Modern Hybrid Cryptography Techniques to Secure Data - Singh Bhathal, Gurjit; Singh Bhathal, Udaibir (International Journal of Computer Sciences and Engineering, 2025)
Cryptography, the practice of concealing messages for private exchange, has evolved significantly to address the challenges posed by new communication methods. In today`s digital world, cryptography has become the cornerstone of cybersecurity, using advanced mathematics like number theory and computational complexity to protect digital information through algorithms. The upcoming arrival of quantum computers poses a serious threat to traditional cryptographic methods, especially those based on asymmetric key cryptography. Quantum Safe Cryptography (QSC) represents the next step in information security, designed to develop cryptographic systems that can withstand attacks from both quantum and classical computers. As quantum computing moves from theory to reality, it`s becoming clear that current cryptographic methods based on integer factorization and discrete logarithm problems are vulnerable to quantum algorithms like Shor`s algorithm. This study highlights the security risks that quantum computing poses to existing encryption methods and proposes a comprehensive approach to quantum-safe cryptography. The transition to quantum-resistant algorithms involves replacing vulnerable cryptographic systems with alternatives that can resist quantum computational attacks. Current analysis shows that while asymmetric key cryptography faces immediate vulnerability, symmetric key algorithms and hash functions remain relatively secure in the near term with appropriate adjustments. Quantum cryptography, which directly uses quantum mechanical principles, offers highly secure encryption mechanisms, notably Quantum Key Distribution (QKD). This research aims to enhance the security of digital infrastructure against quantum threats by evaluating hybrid cryptographic implementations that combine classical and quantum-resistant approaches for optimal security.